Leadership in Action: Morale Victories: How Leaders Can Build Positive Energy - Klann, Gene (Center for Creative Leadership, 2004)
It's not difficult to recognize an organization or team that has strong morale, pride, and spirit as opposed to one that does not. In the former, productivity and creativity are high and relationships are strong; in the latter, negativism, dissatisfaction, and friction reign. Here's a look at some steps leaders can take to enhance the characteristics that make for a prolific, efficient, cooperative, and loyal team.
Keywords: Leadership